Wanted: role models - medical students’ perceptions of professionalism - Byszewski, Anna; Hendelman, Walter; McGuinty, Caroline; Moineau, Geneviève (Université d'Ottawa | University of Ottawa, 2012)
Abstract Background Transformation of medical students to become medical professionals is a core competency required for physicians in the 21st century. Role modeling was traditionally the key method of transmitting this skill. Medical schools are developing medical curricula which are explicit in ensuring students develop the professional competency and understand the values and attributes of this role. The purpose of this study was to determine student perception of professionalism at the University of Ottawa and gain insights for improvement in promotion of professionalism in undergraduate medical education. Methods Survey on student perception of professionalism in general, the curriculum and learning environment at the University of Ottawa, and the perception of student behaviors, was developed by faculty and students and sent electronically to all University of Ottawa medical students. The survey included both quantitative items including an adapted Pritzker list and qualitative responses to eight open ended questions on professionalism at the Faculty of Medicine, University of Ottawa. All analyses were performed using SAS version 9.1 (SAS Institute Inc. Cary, NC, USA). Chi-square and Fischer’s exact test (for cell count less than 5) were used to derive p-values for categorical variables by level of student learning. Results The response rate was 45.6% (255 of 559 students) for all four years of the curriculum. 63% of the responses were from students in years 1 and 2 (preclerkship). Students identified role modeling as the single most important aspect of professionalism. The strongest curricular recommendations included faculty-led case scenario sessions, enhancing interprofessional interactions and the creation of special awards to staff and students to “celebrate” professionalism. Current evaluation systems were considered least effective. The importance of role modeling and information on how to report lapses and breaches was highlighted in the answers to the open ended questions. Conclusions Students identify the need for strong positive role models in their learning environment, and for effective evaluation of the professionalism of students and teachers. Medical school leaders must facilitate development of these components within the MD education and faculty development programs as well as in clinical milieus where student learning occurs.